2013
DOI: 10.1155/2013/382913
|View full text |Cite
|
Sign up to set email alerts
|

A Compact, Versatile Six-Port Radar Module for Industrial and Medical Applications

Abstract: The Six-port receiver has been intensively investigated in the last decade to be implemented as an alternative radar architecture. Plenty of current scientific publications demonstrate the effectiveness and versatility of the Six-port radar for special industrial, automotive, and medical applications, ranging from accurate contactless vibration analysis, through automotive radar calibration, to remote breath and heartbeat monitoring. Its highlights, such as excellent phase discrimination, trivial signal proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A so-called six-port-based CW radar sensor is even capable of measuring movement within the micrometer range [ 38 ]. The six ports include two input and four output ports and have the characteristic that two input signals are superimposed under four relative and static phase shifts which results in four sum signals as output [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…A so-called six-port-based CW radar sensor is even capable of measuring movement within the micrometer range [ 38 ]. The six ports include two input and four output ports and have the characteristic that two input signals are superimposed under four relative and static phase shifts which results in four sum signals as output [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, such systems present some limitations, such as the limited range, the difficulty to operate in the presence of smooth surfaces with a low incidence angle. Recent studies showed the possibility of using electromagnetic radiation for the detection of obstacles placed in front of visually impaired people [5,6].…”
Section: Introductionmentioning
confidence: 99%